1997
DOI: 10.1002/(sici)1097-0134(199703)27:3<425::aid-prot10>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Model-free methods of analyzing domain motions in proteins from simulation: A comparison of normal mode analysis and molecular dynamics simulation of lysozyme

Abstract: Model-free methods are introduced to determine quantities pertaining to protein domain motions from normal mode analyses and molecular dynamics simulations. For the normal mode analysis, the methods are based on the assumption that in low frequency modes, domain motions can be well approximated by modes of motion external to the domains. To analyze the molecular dynamics trajectory, a principal component analysis tailored specifically to analyze interdomain motions is applied. A method based on the curl of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
259
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(268 citation statements)
references
References 32 publications
7
259
1
1
Order By: Relevance
“…This technique has the advantage that it is based on all-atom simulations, with the explicit damping forces and entropic contributions of the solvent, but the resulting modes can only be expressed by giving a 3N -component vector. Hayward et al [16] suggested specifying important modes a priori, and this provides us the great advantage being able to relate the results of several simulations together into a bigger picture. As long as our modes still contain the most important fluctuations, they are a reasonable basis to use.…”
Section: Resultsmentioning
confidence: 99%
“…This technique has the advantage that it is based on all-atom simulations, with the explicit damping forces and entropic contributions of the solvent, but the resulting modes can only be expressed by giving a 3N -component vector. Hayward et al [16] suggested specifying important modes a priori, and this provides us the great advantage being able to relate the results of several simulations together into a bigger picture. As long as our modes still contain the most important fluctuations, they are a reasonable basis to use.…”
Section: Resultsmentioning
confidence: 99%
“…Along this common mode, the DYNDOM method (Hayward et al, 1997; identi®es two subdomains. The ®rst subdomain consists of residues 12-30, 37-83, 510-521 and the second subdomain of 32-34, 90-137, 411-506.…”
Section: Conformational Changes In the Equatorial Domainmentioning
confidence: 99%
“…Modes of collective¯uctuation were analysed for the presence of clear domain motions as described Hayward et al, 1997). This method analyses structural differences in terms of rigid body rotations.…”
Section: Dyndommentioning
confidence: 99%
“…Furthermore, the trajectory of protein motion will rarely be in a straight line, and therefore an otherwise correctly predicted initial direction of motion might deviate noticeably from the observed conformational change (22). Despite these limitations, many studies have found agreement between features of the motion predicted by NMA and the observed or simulated conformational change of one or a small number of proteins (23)(24)(25)(26)(27)(28)(29)(30). A number of large-scale studies have assessed the success of normal modes at describing protein motion as defined by the database of macromolecular movements (31).…”
mentioning
confidence: 99%